The causes and predictors of the 2001 Turkish crisis - Altun, Gurur. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2006., 2006)
2001 was associated with the most serious financial crisis ever experienced in Turkey. The attempts to control two decades of chronic inflation had failed and the country had ended up in a very delicate position. The thesis, keeping in mind that the crisis did not occur just because of the events that took place in 2000 and 2001, tries to provide an explanation in the light of the determinants of real exchange rate. After the introduction of the Turkish economic performance prior to the crisis, the analysis starts with a literature survey. The general currency crisis literature is provided and then Turkey specific crisis literature is thoroughly discussed. The second part focuses on the reasons for devaluation. Based on a survey of the real exchange rate determinants literature, an error correction model is used to detect the long-term determinants of the crisis and the reasons for the crisis turn out to be in line with the real exchange rate determinants literature. Third, the predictability of the crisis is analyzed via a central bank survey data, macroeconomic variables and monetary variables. The results suggest that there were monetary, central bank survey and macroeconomic variables that helped to predict the crisis.
Keywords: Economic crisis -- Turkey.; Financial crises -- Turkey.; Finance -- Turkey -- History -- 20th century.